Scaling Demands of Soccer According to Anthropometric and Physiological Sex Differences: A Fairer Comparison of Men’s and Women’s Soccer - Pedersen, Arve Vorland; Aksdal, Ingvild Merete; Stalsberg, Ragna (Frontiers in Psychology, 2019)
Spectators frequently harass female soccer players and women’s soccer is frequently compared, negatively, to men’s soccer without backing from data, and without taking into account anthropometric and physiological differences between the sexes. This affects female soccer players’ self-confidence negatively, and contributes to an undeserved negative image of women’s soccer. In the present paper, we argue that most differences between men’s and women’s soccer can be explained by the women having to adapt to rules and regulations that are suited for men, and their physical attributes. Thus, games are much more demanding for women. Furthermore, we argue that if men had to play under similar conditions as women do today, they would have to adapt their style of play similarly. As support for our argument, we scale game demands for male and female soccer players according to anthropometric and physiological differences in order to highlight the differences, and use these to predict what would be the most appropriate adaptations. Finally, we show that our predictions are largely supported by the scarce pool of comparable data.